Avalia????o da express??o dos microRNAs, miR-1248, miR-181a E miR- 151a-3p, em idosos portadores de leucemia linfoc??tica cr??nica - Longatti, Simone Cruz (2015)
Aging is a complex and multifaceted process that includes physiological, molecular and genetic changes that lead to functional decline of tissues and organs, leading to increased susceptibility to disease and consequent increase of mortality rates. In this context, chronic non-communicable diseases (NCDs) are often found in the elderly, especially the onco-hematologic diseases, including chronic lymphocytic leukemia (CLL). Considered as essentially a disease of the elderly, CLL is a disease of clonal lymphoid infiltration of B cells found in the bone marrow (BM), peripheral blood and lymph nodes, and characterized as the most common type of leukemia in Western countries. LLC expresses high levels of anti-apoptotic proteins, and decreased levels of proapoptotic proteins, which explains the exaggerated increase of mature B lymphocytes. In addition to changes protein levels, deregulation of microRNAs (miRNAs) have been associated with the LLC. Numerous miRNAs are associated with susceptibility to cancer, suggesting an important role in carcinogenesis. In addition, several miRNAs are also involved in the regulation pathways related to cell senescence and have effects on cell cycle progression, suggesting that miRNAs can be considered good biomarkers in the senescence process. The aim of the study was to evaluate the expression of miRNAs miR- 1248, miR-181a and miR-151a-3p by qPCR in patients with LLC and compare with the elderly group without the disease. The expression of miR-181a was significantly reduced in patients with CLL compared to individuals in the group without LLC. However, the study showed no difference in the expression of miRNAs in the groups with respect to age and sex. It is possible to suggest that these miRNAs can act as regulators likely in aging, however, future studies will determine the mechanism of expression of the same, and to discuss how best to use them as diagnostic and therapeutic tools for aging and age-related diseases such as CLL.